Zebrafish - Perry, Steve F. (Steve Frederick), 1955- (Fish physiology, 2010)
This cutting-edge resource includes up-to-date information on zebrafish physiology and the tools used to study it, not only as a model species for studies of other vertebrates but with application for studies of human disease and aquatic toxicology. The utility of zebrafish for physiological research is based on several key features including i) a "fully" sequenced genome, ii) rapid (~3 month) generation times), iii) their capacity to produce large numbers of externally fertilized eggs, iv) optical transparency of embryos and larvae, and v) the applicability of reverse and forward genetics to.